2015
DOI: 10.1039/c5ra15815j
|View full text |Cite
|
Sign up to set email alerts
|

Band edge movement in dye sensitized Sm-doped TiO2 solar cells: a study by variable temperature spectroelectrochemistry

Abstract: Pure TiO 2 and 8 at.% Sm-doped TiO 2 nanoparticles are prepared via a novel hydrolysis followed by a hydrothermal process at 473 K for 24 h and successfully used into the photoanode of dye sensitized solar cells (DSSCs). The performance of DSSC based on 8 at.% Sm-doped TiO 2 is significantly better compare to DSSC based on undoped TiO 2 . The J sc is 14.53 mA cm -2 and η is 6.78%, which is 15% and 5% higher than that of DSSC based on undoped TiO 2 , respectively. The results of variable temperature spectroelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 45 publications
4
18
0
Order By: Relevance
“…The peak corresponding to the binding energy of 1082.93 eV can be assigned to Sm 3d5/2 [50]. In agreement with previous studies [51], the binding energy of Sm 3d5/2 as revealed in Figure 8i suggested that the chemical state of Sm is +3. The XPS results provided obvious information for the successful doping of HAp with samarium.…”
Section: Resultssupporting
confidence: 91%
“…The peak corresponding to the binding energy of 1082.93 eV can be assigned to Sm 3d5/2 [50]. In agreement with previous studies [51], the binding energy of Sm 3d5/2 as revealed in Figure 8i suggested that the chemical state of Sm is +3. The XPS results provided obvious information for the successful doping of HAp with samarium.…”
Section: Resultssupporting
confidence: 91%
“…The possible down-conversion luminescence mechanism points out that Sm 3+ ions in the 6 H 5/2 ground state are excited to the 6 P 3/2 excited state by absorbing photons with wavelength 395 nm, followed by radiationless deactivation into the 4 G 5/2 , which are the initial levels of the emission 4 G 5/2 → 6 H 5/2 or 4 G 5/2 → 6 H 7/2 . These results are in good agreement with the previous studies [9][10][33][34], which only involved single dopant.…”
Section: Resultssupporting
confidence: 93%
“…It is well known that rare-earth (RE) compounds can efficiently convert incident light from either near-infrared or ultraviolet spectral range to visible range owing to their specific 4f electron structure and unique properties. To increase light absorption range of a solar cell, RE compounds are doped in DSSCs acting as either up-conversion [4][5][6][7][8] or down-conversion luminescent medium [3,[9][10][11][12][13][14][15] to extend the spectral-response range of photo-absorber. Numerous studies have demonstrated that introducing dual dopants from RE group (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The energy band‐gap was calculated from the on‐set of absorption, at lower energies, using the equation Egbold-italic=1240λ0.25em()eV …”
Section: Resultsmentioning
confidence: 99%